2013
DOI: 10.1039/c2sc21553e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of non-hydrolysable diphosphoinositol polyphosphate messengers

Abstract: The diphosphoinositol polyphosphates (PP-IPs) are a central group of eukaryotic second messengers. They regulate numerous processes, including cellular energy homeostasis and adaptation to environmental stresses. To date, most of the molecular details in PP-IP signalling have remained elusive, due to a lack of appropriate methods and reagents. Here we describe the expedient synthesis of methylene-bisphosphonate PP-IP analogues. Their characterization revealed that the analogues exhibit significant stability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 43 publications
0
90
0
5
Order By: Relevance
“…IP6K1-generated 5-IP7 modulates cell metabolism, signaling, exocytosis, and migration (48,(55)(56)(57)(58). IP6K1-generated 5-IP7 regulates insulin signaling by inhibiting the insulin-sensitizing protein kinase Akt both in vivo and in vitro (58)(59)(60)(61), whereas it promotes insulin secretion from pancreatic β cells (57). IP6K1 also regulates global transcription by 5-IP7-mediated inhibition of the histone demethylase JMJD2C (62).…”
Section: Resultsmentioning
confidence: 99%
“…IP6K1-generated 5-IP7 modulates cell metabolism, signaling, exocytosis, and migration (48,(55)(56)(57)(58). IP6K1-generated 5-IP7 regulates insulin signaling by inhibiting the insulin-sensitizing protein kinase Akt both in vivo and in vitro (58)(59)(60)(61), whereas it promotes insulin secretion from pancreatic β cells (57). IP6K1 also regulates global transcription by 5-IP7-mediated inhibition of the histone demethylase JMJD2C (62).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that we were detecting cleavage of the pyrophosphate of 5PP-IP 5 , we tested the ability of Siw14 to utilize analogs of IP 7 that contain non-hydrolyzable methylene-bisphosphonate moieties (13,14). In these analogs, carbon replaces the oxygen in the anhydride linkage to the ␤-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…IP 6 was purchased from Sigma. Four isoforms of IP 7 (5-diphosphoinositol pentakisphosphate (5PP-IP 5 ), non-hydrolyzable 5-methylene-bisphosphonate inositol pentakisphosphate (5PCP-IP 5 ), 1PP-IP 5 , and non-hydrolyzable 1-methylene-bisphosphonate inositol pentakisphosphate (1PCP-IP 5 )) and IP 8 (3,5-bisdiphosphoinositol tetrakisphosphate (3,5PP-IP 4 )) were synthesized following the methods described previously (13)(14)(15).…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…40 Although one report showed that IP 7 is not able to displace PI(3,4,5)P 3 from AKT in an in vitro binding assay, 77 it was later demonstrated that non-hydrolysable analogues of 5-IP 7 or 1-IP 7 can inhibit AKT activation even in the presence of PI(3,4,5)P 3 . 78 A recent study revealed that chemically synthesized 5-IP 7 released into mammalian cells is able to induce translocation of AKT from the plasma membrane to the cytoplasm. 79 It has been shown that AKT and other PH domains bind 5-IP 7 and IP 6 with higher affinity as compared with 1-IP 7 or IP 8 .…”
Section: Plasma Membranementioning
confidence: 99%
“…78,79,[126][127][128][129] Highly pure PP-IPs with β-phosphate moieties at specific carbon atoms have been synthesized by these groups, including non-hydrolysable analogues that are stable in cells and can bind target proteins but not pyrophosphorylate them. 47,78,130 A system for intracellular delivery and photouncaging of chemically synthesized PP-IPs has recently been developed, 79 which promises to open up new methods to study the functions of these molecules in different subcellular compartments. The use of IP 7 as an affinity reagent revealed two different classes of interacting proteins, depending on the absence or presence of the divalent cation Mg 2+ during the interaction, representing IP 7 binding or pyrophosphorylation targets respectively.…”
Section: Perspective On the Futurementioning
confidence: 99%